Risk factors for gestational hypertension at RSIA Sitti Khadijah 1 year 2019-2022 - Ainun Jariah Fahay; Fadli Ananda; Nur Fatimah Sirajuddin; M. Hamsah; Susiawaty, Susiawaty (Jurnal EduHealth, 2024)
Gestational hypertension (also called transient hypertension) is hypertension that occurs in pregnancy without proteinuria. This research was conducted at RSIA Khadijah Makassar 1 year 2019-2022, using a retrospective descriptive method, using total quota sampling that met the inclusion criteria. The number of samples obtained was 32 samples with the characteristics of gestational hypertension occurring most frequently at the age of 20-35 years, namely 26 (81.25%), with grand multigravida, namely 13 (40.6%), BMI >25 kg/m2 27 ( 84.4%), and in patients without a history of hypertension, namely 17 (53.12%). Based on statistical tests, it was found that there is a relationship between gravida and the incidence of gestational hypertension with a p-value of 0.083, which is smaller than 0.10, meaning that pregnant women with primigravida and grand multigravida have a 9.3 times higher risk of developing gestational hypertension than pregnant women. with multigravida, while age, BMI, and history of hypertension had no significant relationship to the incidence of gestational hypertension at RSIA Sitti Khadijah 1. .